Hospital mortality in COVID-19 patients in Belgium treated with statins, ACE inhibitors and/or ARBs - Geert Byttebier; Luc Belmans; Myriam Alexander; Bo E. H. Saxberg; Bart De Spiegeleer; Anton De Spiegeleer; Nick Devreker; Jens T. Van Praet; Karolien Vanhove; Reinhilde Reybrouck; Evelien Wynendaele; David S. Fedson (Taylor & Francis Group, 2021)
The COVID-19 pandemic has disrupted life throughout the world. Newly developed vaccines promise relief to people who live in high-income countries, although vaccines and expensive new treatments are unlikely to arrive in time to help people who live in low-and middle-income countries. The pathogenesis of COVID-19 is characterized by endothelial dysfunction. Several widely available drugs like statins, ACE inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) have immunometabolic activities that (among other things) maintain or restore endothelial cell function. For this reason, we undertook an observational study in four Belgian hospitals to determine whether in-hospital treatment with these drugs could improve survival in 959 COVID-19 patients. We found that treatment with statins and ACEIs/ARBs reduced 28-day mortality in hospitalized COVID-19 patients. Moreover, combination treatment with these drugs resulted in a 3-fold reduction in the odds of hospital mortality (OR = 0.33; 95% CI 0.17-0.69). These findings were in general agreement with other published studies. Additional observational studies and clinical trials are needed to convincingly show that in-hospital treatment with statins, ACEIs/ARBs, and especially their combination saves lives.